Audio Book: Teaching Listening Comprehension - Khairul Fajry; Endang Komariah; Tengku Maya Silvianti (Research in English and Education Journal, 2016)
This study was aimed at finding out whether the implementation of audio book with narrative story can enhance students’ listening comprehension of SMA Negeri 1 Ingin Jaya Aceh Besar. The population of this study was the second grade students from the second semester and the sample was the students in 2 IPA1. The framework used in this research was suggested by (Antonaccy, O’callaghant, Berkowitz, 2015 Burkey, 2013), while the design of this study was a pre-experimental study. To obtain the data, the researcher used 10 items of multiple choice question in pre-test and post-test. The result of data collection in this study shows that average post-test score is higher (74.44) than the pre-test score (36.66). The result of the difference scores both of the test is 37.78. The result of hypothesis test is higher than critical value of t-table (t- tt- 2.06). It means Ha is accepted and Ho is rejected or in other words, audio book with narrative story can enhance students’ listening comprehension. In conclusion, audio book is recommended as good media in language teaching and learning listening skill.